Genomic Analysis of the Yet-Uncultured Binatota Reveals Broad Methylotrophic, Alkane-Degradation, and Pigment Production Capacities - Chelsea L. Murphy (American Society for Microbiology, 2021)
A wide range of microbial lineages remain uncultured, yet little is known regarding their metabolic capacities, physiological preferences, and ecological roles in various ecosystems. We conducted a thorough comparative genomic analysis of 108 genomes belonging to the Binatota (UBP10), a globally distributed, yet-uncharacterized bacterial phylum.